Long-married couples recall their wedding day: the influence of collaboration and gender on autobiographical memory recall. Issue 1 (2nd January 2020) - Grysman, Azriel; Harris, Celia B.; Barnier, Amanda J.; Savage, Greg
ABSTRACT: The current study examined the influence of collaboration, expertise, and communication on autobiographical memory, by considering gender differences in recall and how they may influence the products and processes of remembering when male-female couples recall events together. Thirty-nine long-married, male-female couples recalled their memories of their wedding day. In Session 1, they recalled it individually for an experimenter. One week later, in Session 2, they recalled the same event jointly as a collaborative pair. Women reported more details, especially episodic details, than men across both sessions. Notably, collaborative recall included many new details that neither spouse had recalled individually. Exploratory analyses suggest that women were less influenced by collaboration than were men: women's communication behaviours influenced men's recall, but the reverse was not found for men's communication. Additionally, when couples' individual recall was more similar in content, men were more likely to decrease their contribution to the collaborative session. We consider these findings in light of transactive memory theory, in which joint meta-memory and the distribution of expertise influence the processes and products of recall in the interdependent system of a couple who extensively share their autobiographical memories.